Efficacy of an Individualized Computer-Assisted Social Competence Training Program for Children With Oppositional Defiant Disorders/Conduct Disorders - Goertz-Dorten, Anja; Groth, Manuela; Detering, Kerstin; Hellmann, Anne; Stadler, Laura; Petri, Barbara; Doepfner, Manfred (Frontiers in Psychiatry, 2019)
Group-based child-centered cognitive-behavioral therapy (CBT) for children with aggressive behavior has been found to significantly reduce child behavior problems. Nevertheless, most children suffer from residual symptoms at the end of treatment. Therefore, individualized interventions that treat the specific problem-maintaining factors and that use digital support may enhance treatment effects. However, enhanced computer-facilitated interventions have not been examined in clinical samples. Therefore, we tested the efficacy of an individualized computer-facilitated social skills training for children with clinically referred aggressive behavior problems. Fifty children aged 6-12 years with peer-related aggressive behavior problems were included in a within-subject design with two phases (waiting, treatment). The course of the outcome measures during an eight-week waiting phase was compared with that in the subsequent treatment phase (16 weekly child sessions and two parent psychoeducation contacts at the beginning of the treatment) using multilevel modeling. The primary outcome was peer-related aggressive behavior rated by parents. Further outcome measures included parent ratings and patient self-reports of aggressive and prosocial behavior. No significant changes occurred for any of the outcome variables during the waiting phase. During treatment, most parent-rated outcome measures (including the primary outcome measure) showed a significant decrease, which was stronger than changes in the waiting phase. Most self-rated outcome measures also showed significant decreases during treatment, but a stronger decrease than in the waiting phase was only found for peer-related aggressive behavior. The computer-facilitated social skills training appears to be an effective CBT intervention for children with peer-related aggressive behavior.